E0393 Significance of oxidised low-density lipoproteinin coronary atherosclerotic heart disease. (17th November 2010) - Meng, Xiaoping; Li, Chang
Abstract : Objective: In this study, control group are people with normal coronary arteries. This study is to discuss the relationship between LDL, OX-LDL and control group, SAP group, UAP group, AMI guoup and contaction of LDL and OX-LDL. Methods: Experimental group are 300 CHD patients without taking lipid-lowering drugs in one month who admittde in the depatrment of cardiolysis from August 2008 to August 2009. They are divided into SAP group (100 cases), UAP group (100 cases), AMI (100 cases). The control group are 100 cases of patients who are randomly selected and confirmed without CHD by coronary angiography in the same period in our department. Information includs gender, age, smoking, drinking, hypertension, diabetes, levels of LDL and OX-LDL. We analysis patients' basic information, the level and correlation of LDL and OX-LDL in control group, SAP group, UAP group and AMI group. Results: 1. There are no significant differents between control group and CHD groups in basic information (p>0.05). 2. Concentration of LDL in CHD group is significant difference compared with control group (p<0.01). Concentration of LDL in UAP group is no significant difference compared with SAP group (p>0.05). Concentration of LDL in AMI group is significant difference compared with SAP group (p<0.01). Concentration of LDL in AMI group is no significant difference compared with UAP group (p>0.05). 3. Concentration of OX-LDL in CHD group is significant difference compared with control group (p<0.01). Concentration of OX-LDL in UAP group is significant difference compared with SAP group (p<0.05). Concentration of OX-LDL in AMI group is significant difference compared with SAP group (p<0.01). Concentration of OX-LDL in AMI group is significant difference compared with UAP group (p<0.01). 4. There is no correlation between concentration of LDL and OX-LDL in all groups (p>0.05). Conclusions: 1. We confirm that LDL and OX-LDL are risk factors for CHD. There is no significant differences about the concentration of LDL in CHD groups, however, there is significant differences about the concentration of OX-LDL in CHD groups. The level of OX-LDL is in escalating trend. 2 There is no correlation between concentration of LDL and OX-LDL in all groups (p>0.05) and OX-LDL play a more important role in the process of CHD. Compared with LDL, mensurating OX-LDL is more meaningful in the treatment and prevention of CHD.